On the Optimality of Decisions - Jan Marc Berk; Beata Bierut (Tinbergen Institute, 2004)
Most monetary policy committees decide on interest rates using a simple majority voting rule. Given the inherent heterogeneity of committee members, this voting rule is suboptimal in terms of the quality of the interest rate decision, but popular for other (political) reasons. We show that a clustering of committee members into 2 subgroups, as is the case in a hub-and spokes systems of central banks such as the Fed or the ESCB, can eliminate this suboptimality whilst retaining the majority voting rule.
Keywords: D71; D78; E58; 330; central banks' policies; decision-making under uncertainty; committees; decision-making processes; Zentralbank; Zinspolitik; Entscheidung; Abstimmungsregel